Proceedings of the 8th Conference on Human-Computer Interaction With Mobile Devices and Services 2006
DOI: 10.1145/1152215.1152260
|View full text |Cite
|
Sign up to set email alerts
|

Target size study for one-handed thumb use on small touchscreen devices

Abstract: This paper describes a two-phase study conducted to determine optimal target sizes for one-handed thumb use of mobile handheld devices equipped with a touch-sensitive screen. Similar studies have provided recommendations for target sizes when using a mobile device with two hands plus a stylus, and interacting with a desktop-sized display with an index finger, but never for thumbs when holding a small device in a single hand. The first phase explored the required target size for single-target (discrete) pointin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
187
3
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(214 citation statements)
references
References 18 publications
10
187
3
6
Order By: Relevance
“…In particular, the success rate of 67mm device was higher than that of other devices and the results of rest devices were similar. This result is in line with findings of previous works (Colle and Hiszem, 2004;Hwangbo et al, 2013;Parhi et al, 2006, September) We expected that the results of task completion time were similar with those of success rate. However, the task completion time of 67mm devices was poor regardless of task difficulties.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, the success rate of 67mm device was higher than that of other devices and the results of rest devices were similar. This result is in line with findings of previous works (Colle and Hiszem, 2004;Hwangbo et al, 2013;Parhi et al, 2006, September) We expected that the results of task completion time were similar with those of success rate. However, the task completion time of 67mm devices was poor regardless of task difficulties.…”
Section: Discussionsupporting
confidence: 93%
“…However, their study setup included a fixed tablet in a specific angle, which is quite different from the normal usage of a smartphone. These target sizes contrast with the 9-10mm suggested by other studies [40,41]. A more recent study [26] reported that older adults have the best accuracy when tap targets on the smartphone have between 14 and 17.5mm, with 10mm being acceptable when screen space is restricted.…”
Section: Touchscreen Interaction Of Older Peoplementioning
confidence: 69%
“…From the press point error distribution we calculated the 98 percentile points in positive and negative directions for both x and y. Taking the approach described by [39], this defines the bounding rectangle that captures 95% of user presses. As the distributions are slightly skewed to either positive or negative sides, and in practice it is not possible to position a touch target at the exactly the correct offset from the center, thus we take double the larger absolute value, which may be considered as the minimum size for targets in the UI.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that these values are based on index finger usage, as in the test protocol. For thumb usage sizes will be somewhat larger (see [39]). The minimum target sizes are shown in Table 2. and diagrammatically in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation